(untitled) (Terr@ Plural, 2020)
This study evaluated the degree of infestation of hemiparasites of the family Loranthaceae in the urban street trees of Blumenau in 200 random sample points considering a buffer of 100 m. It was identified 19 families, 33 genera, and 39 species, counting 167 trees. From these, 66% were exotic species, 17.3% with some degree of infestation. By contrast, only 1.97% of native species were infected with mistletoe. Heat maps indicate that the highest density of infested trees occurred in central areas of the city where the presence of street trees is greater and, consequently, the possibility of contagion. Intervention is recommended in affected individuals through manual pruning and removal of the hemiparasites. Given the susceptibility of infestation in exotic trees, it is recommended to be replaced by species less susceptible.